2008
DOI: 10.1083/jcb.200808105
|View full text |Cite
|
Sign up to set email alerts
|

Collective cell migration requires vesicular trafficking for chemoattractant delivery at the trailing edge

Abstract: Chemoattractant signaling induces the polarization and directed movement of cells secondary to the activation of multiple effector pathways. In addition, chemotactic signals can be amplified and relayed to proximal cells via the synthesis and secretion of additional chemoattractant. The mechanisms underlying such remarkable features remain ill defined. We show that the asymmetrical distribution of adenylyl cyclase (ACA) at the back of Dictyostelium discoideum cells, an essential determinant of their ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
110
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(125 citation statements)
references
References 61 publications
10
110
0
3
Order By: Relevance
“…13, upper row, left) a trail of secreted ACA vesicles was observed. This behavior is in agreement with the localization and secretion of ACA vesicles in wild-type cells (58). In contrast, ACA-YFP in cells expressing F-Y/A-actin (Fig.…”
Section: Cell Numbersupporting
confidence: 73%
“…13, upper row, left) a trail of secreted ACA vesicles was observed. This behavior is in agreement with the localization and secretion of ACA vesicles in wild-type cells (58). In contrast, ACA-YFP in cells expressing F-Y/A-actin (Fig.…”
Section: Cell Numbersupporting
confidence: 73%
“…Although both models are capable of reproducing many features of Dictyostelium aggregation, including the propagation of cAMP waves in characteristic spirals and the formation of stream-like aggregates, they are not perfect. In previous work, we have proposed that the secretion of cAMP is spatially restricted (Kriebel et al, 2003(Kriebel et al, , 2008. We now show that only the secreted form of PdsA can degrade the external cAMP signal and that the addition of a uniform bolus of PdsA does not lead to the formation of highly branched, head-to-tail lines characteristic of WT streaming.…”
Section: Discussionmentioning
confidence: 52%
“…Interestingly, as cells form aggregates, they acquire the ability to migrate in groups by aligning in a head-to-tail manner, forming characteristic streams. We have previously shown that the ability of cells to stream depends on the enrichment of ACA-containing vesicles at the back of migrating cells (Kriebel et al, 2003(Kriebel et al, , 2008. We propose that the formation of head-to-tail arrays is regulated by the specific release of cAMP from vesicles at the back of cells.…”
Section: Introductionmentioning
confidence: 82%
“…In general, a response to a step stimulus may not necessarily have the same propensity as that for a slowly varying stimulus. Moreover, directional migration is induced by a traveling-wave stimulus (17,18) and thus may affect the cAMP relay owing to a large overlap in the signal transduction network (16,31,32). To test relevance of the fold-change response property for natural cAMP wave, we used a microfluidics lighthouse (33)-a gradient-generating platform capable of delivering traveling-wave stimulus of various amplitude, frequencies, and speed.…”
Section: Resultsmentioning
confidence: 99%